Politik Identitas dan Representasi Inklusif: Dinamika Partisipasi Suku Marind dalam Parlemen Lokal Merauke - Wika, Martinus (Indo Publishing, 2025)
This study aims to analyze the dynamics of Marind participation in the Merauke local parliament, identify the structural and cultural barriers faced, and formulate strategies to realize more inclusive representation. A qualitative case study approach is used to explore in depth the process, meaning, and complexity of Marind political participation in a specific local context that is full of cultural, historical, and power relations nuances. Data were collected through in-depth interviews, participant observation, and document studies involving 15 purposively selected key informants, consisting of local parliament members, traditional leaders, political elites, civil society activists, and technical officials. The results of the study indicate that Marind political participation in the local parliament is still symbolic and has not been effective in fighting for the substantive interests of the indigenous community. The main obstacles identified include the dominance of non-Marind elites in political parties, weak local affirmative regulation, internal fragmentation of the Marind Tribe, and limited community-based political cadre formation. This study recommends a multi-level strategy to strengthen inclusive representation, including strengthening community political education, formulating affirmative policies, and increasing multi-party dialogue. These findings provide important contributions to the development of literature on identity politics and inclusive representation, and offer practical recommendations for improving local political systems in multicultural areas such as Merauke.